The complexity of national identity Construction in Curaçao, Dutch Caribbean - Allen, Rose Mary (European Review of Latin American and Caribbean Studies, 2010)
Curaçao, one of the five islands of the Dutch Caribbean federation called the Netherlands Antilles, currently stands at a crossroad of constitutional reform. In the context of these changes at the political level, it is logical that national identities are being redefined and repositioned. The developments in the fashioning of national identities in Curaçao deserve attention locally but also regionally. How do people in Curaçao construct national identities in daily life? How is a national collective constructed on the one hand, and how are differences with other collectivities constructed on the other hand? The historical context of constitutional changes that have occurred over the years is considered as well as an examination of the present discourse on constitutional reform. These identity issues are then placed within a wider Caribbean context. Resumen: La complejidad de la construcción de la identidad nacional en Curaçao,en el Caribe holandés Curaçao, una de las cinco islas de la federación caribeña neerlandesa llamada Antillas Holandesas, se encuentra hoy en día en una encrucijada de reformas constitucionales. En el contexto de estos cambios a nivel político, es lógico que las identidades nacionales sean redefinidas y reposicionadas. Los desarrollos en la formulación de identidades nacionales en Curaçao merecen atención local, y también regional. ¿Cómo construye la gente en Curaçao identidades nacionales en la vida cotidiana? ¿Cómo, por un lado, se construye el colectivo nacional y, por otro, cómo se construyen las diferencias con otras colectividades? En este análisis se estudia el contexto histórico de los cambios constitucionales que han ocurrido en el curso del tiempo y se realiza igualmente una revisión del actual discurso sobre la reforma constitucional. Estos problemas de identidad son analizados entonces en un contexto caribeño más amplio.